Judicial review of commercial contracts: a comparative handbook - Wais, Hannes; Pfeiffer, Thomas (Beck International, 2022)
Judicial Review of Commercial Contracts This book presents a broad survey of standards for the judicial control of b2b-contract terms in different legal systems. Each chapter analyses in great detail the regulatory framework and the general principles that govern the judicial control of b2b-contracts in a specific county, in particular the relevant standards for the judicial scrutiny of clauses and the resulting legal consequences thereof. Providing first-hand information with a focus on practical relevance from authors who specialize in the judicial control of contracts in their respective legal system, this book is of particular value for lawyers who advise their clients in international business transactions and anyone interested in comparative contract law. The list of countries includes Austria, the Czech Republic, Denmark, England, Estonia, Finland, France, Germany, Italy, the Netherlands, Poland, Portugal, Romania, Spain, Switzerland, Sweden and Taiwan.